Long-term outcomes of untreated micropenis: growth patterns and predictive factors - Amirkashani, Davoud; Abdollahi Sarvi, Mostafa; Masoumi, Mostafa (Frontiers in Pediatrics, 2025)
BackgroundMicropenis, defined as a penile length more than 2.5 standard deviations below the mean for age and population, presents significant concerns for patients and parents. Despite current guidelines recommending multidisciplinary management, there is limited evidence on long-term outcomes, particularly in untreated patients.MethodsThis prospective cohort study involved 46 male children aged 7–9 years presenting with micropenis at the Ali Asghar Endocrine Clinic from 2015 to 2023. Initial penile size, BMI, and other growth parameters were measured, with biannual follow-ups extending 3 years post-bone fusion to evaluate growth rates and influential factors.ResultsInitial mean stretched penile length (SPL) was 3.22 ± 0.21 cm. Significant increases in penile size were observed across all intervals, with the highest growth rates occurring between the first- and second-years post-fusion. BMI emerged as the most significant predictor of penile growth, while initial SPL was the least influential factor. By the third-year post-fusion, the vast majority of subjects (44) achieved penile lengths within the normal range. Two patients, while showing penile growth over time, remained below the cutoff value defined by reference standards.ConclusionOur findings indicate that most untreated micropenis patients reach normal penile size by adulthood, highlighting the importance of monitoring growth rates rather than focusing only on initial penile size. This study provides critical insights for developing guidelines and management strategies for micropenis, emphasizing the necessity of continued follow-up to ensure optimal outcomes.